Effect of Curcuma zedoaria Rosc root extracts on behavioral and radiology changes in arthritic rats - Madan L Kaushik; Sunil S Jalalpure (Wolters Kluwer Medknow Publications, 2011)
The present study was conducted to evaluate the effects of petroleum ether, chloroform, and methanol root extracts of Curcuma zedoaria Rosc (Family: Zingiberaceae) on behavioral and radiology aspects of Freund's Complete Adjuvant (FCA)-induced monoarthritis in left ankle joint of rats using open-field test. Traditionally, Curcuma zedoaria root has been used as anti-inflammatory and antiarthritic drug. Behavioral aspects include latency time to explore, ambulatory, rearing, grooming, urination, and defecation. Animals were divided into ten groups each of six rats, all the animals were subjected to open-field test before the induction of arthritis at 0 day and thereafter 3, 7, 14 21, 28, 35, and 42 days of postinoculation FCA injection. The rat was placed in an open field and observed all behavioral aspects for 5 minutes and radiography analysis was made on day 42. Selected doses were 10 mg/kg.i.p. Indomethacin 200 mg/kg.p.o. marketed herbal drug Rumalaya forte and 200 and 400 mg/kg.p.o. of each extracts, respectively. The results showed significant decrease in ambulation and rearing; however, increase in latency time to explore and grooming, urination, and defecation in control group, but in contrast, drug-treated groups showed significant recovery in all behavioral aspects except methanol groups. On the basis of radiography examination, control and methanol groups showed highest swelling compared with normal group; however, all drug-treated groups showed significant reduced swelling. Treatments with petroleum ether and chloroform extracts recovery were observed in behavioral and radiological aspects in arthritic rats.